Compositions for enhancing the electroactive properties of fluorinated polymers - Patents.com
Patent Information
- Application Number
- JP2024545806
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-01
- Filing Date
- 2023-01-31
- Publication Date
- 2025-02-21
Smart Images

Figure 2025505140000001 
Figure 2025505140000002 
Figure 2025505140000003
Abstract
Description
[Technical field]
[0001] This application relates to electroactive polymers in a liquid vehicle, often referred to as electroactive polymer inks.
[0002] More specifically, this application is directed to compositions comprising copolymers including repeat units derived from vinylidene fluoride and trifluoroethylene in a liquid vehicle.
[0003] The compositions can be used to form polymer layers, often referred to as coatings or films, that have enhanced electroactive properties, which can be of particular interest in electronic devices. [Background technology]
[0004] Ferroelectric materials are a class of crystalline or semi-crystalline materials that exhibit hysteresis in the polarization-electric field curve. These materials have a phase transition between ferroelectric and paraelectric phases at the Curie temperature.
[0005] At a given temperature below the Curie transition, the polarization hysteresis curve is characterized by the coercivity (Ec) (the absolute value of the electric field at zero polarization) and the remanent polarization (Pr) (the absolute value of the polarization at zero applied electric field)
[0006] Piezoelectricity is the ability of some materials to convert mechanical energy into electrical energy and vice versa. When a piezoelectric material is subjected to a mechanical input (deformation, force, vibration, etc.), a charge or voltage is generated on the surface of the material (direct piezoelectric effect). The direct piezoelectric effect of ferroelectric materials is due to a change in polarization induced by a mechanical stimulus.
[0007] Due to its ferroelectric structure and its piezoelectric properties, P(VDF-TrFE) is a base material for electronic devices, e.g. printed sensors for measuring pressure, force, deformation, acoustic vibrations, etc.
[0008] Scientific publications: Ohigashi, H., & Hattori, T.(1995).Improvement of piezoelectric properties of poly(vinylidene fluoride) and its copolymers by crystallization under high pressures. Ferroelectrics,171(1),11-32 teach that in general, the piezoelectric activity of an electroactive polymer is proportional to its remnant polarization, which in turn is proportional to its crystallinity (see first paragraph on page 12).
[0009] In addition, the literature Nguyen, QD, Venkatesan, TR, Wirges, W., & Gerhard, R. (July 2019). Non-uniform polarization profiles in P(VDF-TrFE) copolymer films after cyclical poling, IEEE International Symposium on Ferroelectric Applications (ISAF) 2019 (pages 1-4) also reports that a commercially available P(VDF-TrFE) copolymer film with a molar ratio of VDF:TrFE of 75:25 exhibits a polarization profile of 70 mC / m when poled at an electric field of 100 MV / m. 2 (Meaning: 7.0μC / m 2 ) is known to have a measured remnant polarization.
[0010] Ohigashi studies the effect of high pressure crystallization on the properties of ferroelectric polymers. It shows in particular that crystallizing some P(VDF-TrFE) copolymers at very high pressure, typically hundreds or thousands of bar, can be beneficial to enhance their piezoelectric activity. However, the method only results in a crystallization of 95 mC / m for a P(VDF-TrFE) copolymer with, for example, a molar ratio of VDF:TrFE of 75:25. 2 Although it is interesting to imagine the possibility of reaching high remanent polarizations (see Table 1, no electric field for poling is mentioned), this is extremely difficult to implement in practice and completely impractical on an industrial scale.
[0011] There is currently a need to fabricate one or more polymer layers, particularly films or coatings, of fluorinated polymers comprising repeat units derived from vinylidene fluoride and trifluoroethylene, with improved electroactive properties, particularly with higher remanent polarization, also referred to as Pr. [Prior art documents] [Non-patent literature]
[0012] [Non-Patent Document 1] Ohigashi, H., & Hattori, T. (1995).Improvement of piezoelectric properties of poly(vinylidene fluoride) and its copolymers by crystallization under high pressures. Ferroelectrics,171(1),11-32 [Non-Patent Document 2] Nguyen, Q.D., Venkatesan, T.R., Wirges, W., & Gerhard, R. (July 2019). Non-uniform polarization profiles in P(VDF-TrFE) copolymer films after cyclical poling, 2019 IEEE International Symposium on Ferroelectric Applications (ISAF) (pp. 1-4) Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention aims to provide a composition adapted to produce such a polymer layer and said polymer layer.
[0014] SUMMARY OF THE PRESENT EMBODIMENT A first object of the present invention is directed to a composition comprising a fluorinated polymer and a liquid vehicle. [Means for solving the problem]
[0015] The fluorinated polymer comprises repeat units derived from vinylidene fluoride and trifluoroethylene, and the fluorinated polymer has a melt flow index of 6 g / 10 min to 16 g / 10 min, measured at 230° C. under a load of 10 kg according to ASTM D1238-20.
[0016] The liquid vehicle is (Ra) 2 Hansen solubility parameter (δ) of ≦22 d ;δ p ;δ h ) and Ra is defined as follows: (Ra) 2 =4·(δ d -17.1) 2 +(δ p -12.6) 2 +(δ h -10.6) 2 (Equation 1)
[0017] Preferably, the fluorinated polymer has a melt flow index, measured according to ASTM D1238-20 at 230° C. under a load of 10 kg, of 8 g / 10 min to 15 g / 10 min, more preferably 10 g / 10 min to 14 g / 10 min.
[0018] In some particular embodiments, the fluorinated polymer has a melt flow index of 11 g / 10 min to 13 g / 10 min, measured according to ASTM D1238-20 at 230° C. under a load of 10 kg.
[0019] In some embodiments, the fluorinated polymer also comprises one or more repeat units derived from a fluorinated monomer of formula (I). CX1X2=CX3Z-(I) [wherein each of X1, X2 and X3 is independently selected from H, F and an alkyl group containing 1 to 3 carbon atoms which may be partially or fully fluorinated, and Z is selected from Cl, Br and I.]
[0020] In some preferential embodiments in which the fluorinated polymer comprises one or more repeat units derived from a fluorinated monomer of formula (I), such repeat units are advantageously chlorotrifluoroethylene, chlorofluoroethylene, or a combination thereof.
[0021] The inventors have surprisingly found that by a) selecting a very specific range of melt flow indexes of fluorinated polymers and b) selecting Hansen solubility parameters (δ) such that the distance to the center having coordinates (17.1, 12.6, 10.6), calculated as "Ra", is sufficiently short. d , δ p , δ H It has been found that the combination of a fluorinated polymer layer, such as a coating or film, with the selection of a liquid vehicle having improved electroactive properties, in particular a higher remanent polarization, can be obtained.
[0022] In some embodiments, the fluorinated polymer consists essentially of or consists of repeat units derived from vinylidene fluoride, trifluoroethylene and optionally one or several fluorinated monomers of formula (I), the molar ratio of trifluoroethylene being between 15% and 50%, preferentially between 16% and 35%, most preferentially between 17% and 32%, relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units in the polymer. The molar ratio of repeat units derived from one or several fluorinated monomers of formula (I) being between 0% and 15%, preferentially between 1% and 10%, relative to the total molar amount of all repeat units in the polymer.
[0023] In some embodiments, the liquid vehicle is (Ra) 2 ≦15, preferentially (Ra) 2 ≦8, preferentially (Ra) 2 ≦6, preferentially (Ra) 2 ≦4, most preferentially (Ra) 2 It has a Hansen solubility parameter of ≦3.
[0024] In some embodiments, the liquid vehicle consists essentially of, or consists of, dimethylsulfoxide, tetramethylurea, diethylene glycol monoethyl ether, N-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, trimethyl phosphate, triethyl phosphate, dimethylformamide, dimethylacetamide, and mixtures thereof.
[0025] Preferentially, the liquid vehicle consists essentially of or consists of N-methyl-2-pyrrolidone, trimethyl phosphate, triethyl phosphate, dimethylformamide, dimethylacetamide, and mixtures thereof.
[0026] More preferentially, the liquid vehicle consists essentially of or consists of triethyl phosphate, dimethylformamide, dimethylacetamide and mixtures thereof.
[0027] In some particular embodiments, the liquid vehicle consists essentially of, or consists of, dimethylformamide, dimethylacetamide, and mixtures thereof.
[0028] In some embodiments, the mass concentration of the fluorinated polymer in the liquid vehicle is from 0.1% to 50%, preferably from 1% to 30%, and most preferably from 5% to 20%.
[0029] The invention also relates to a polymer layer obtained by a process comprising a step of deposition of a composition according to the invention, the step comprising removing the liquid vehicle from the composition.
[0030] In some embodiments, the coating step is carried out by one of the techniques selected from the group consisting of: spin coating, spray coating, bar coating, slot-die coating, dip coating, roll-to-roll printing, screen printing, flexographic printing, lithographic printing, inkjet printing, preferably spin coating.
[0031] In some embodiments, the polymer layer has an average thickness of from 100 nm to 100 μm, preferably from 500 nm to 50 μm, more preferably from 750 nm to 20 μm, and most preferably from 1 μm to 10 μm.
[0032] In some embodiments, the process includes annealing the fluorinated polymer below its melting temperature.
[0033] In some embodiments, the process includes a poling step. Indeed, the domains of fluorinated polymers containing repeat units derived from vinylidene fluoride and trifluoroethylene are usually randomly oriented. Poling cannot align these domains by applying a strong electric field in a manner known to those skilled in the art.
[0034] The invention finally relates to an electronic device comprising a polymer layer according to the invention, preferably selected from field effect transistors, memory devices, capacitors, sensors, actuators, Microelectromechanical Systems (MEMS), wearable electrical devices market, robotic sensors and haptic devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The invention will now be explained in more detail in the following description, without being limited thereto.
[0036] In the present description, the term "a" or "an" means "at least one." Thus, a composition comprising a fluorinated polymer and a liquid vehicle refers to a solution comprising at least one fluorinated polymer and at least one liquid vehicle.
[0037] The phrase "polymer consisting essentially of repeating units" means that the polymer contains at least 99 mol %, or at least 99.5 mol %, or at least 99.9 mol % of these units, based on the total number of moles of units that make up the polymer.
[0038] The melt flow index of a polymer, abbreviated as MFI, is measured according to ASTM D1238-20 at 230° C. under a load of 10 kg. It is expressed in grams / 10 min (g / 10 min).
[0039] The melting temperature of the polymer corresponds to the peak temperature during the second heating, measured by differential scanning calorimetry (DSC) analysis according to ASTM D3418-15 using a ramp of 10° C. / min. The Curie transition temperature of the polymer is a first order transition and can be measured under the same conditions as the melting temperature.
[0040] As used herein, suitable solvents are defined as those having a Hansen solubility parameter (δ d ;δ p ;δ h The Hansen solubility parameters have been developed by Charles M. Hansen since 1967 as a way to predict whether one material will dissolve in another to form a solution. The parameter "δ d " is related to the energy from dispersion forces between molecules. The parameter "δ p " is related to the energy from dipole-dipole intermolecular forces between molecules. The parameter "δ h " is related to the energy from hydrogen bonds between molecules. The Hansen solubility parameter is in MPa (1 / 2) It is expressed as:
[0041] Hansen solubility parameter (δ d ;δ p ;δ h) have been evaluated for a long time for the most commonly used solvents and are now collected in data tables. The Hansen Solubility Parameters of the different liquid vehicles mentioned in this specification were taken from CM (2007). Hansen Solubility Parameters: A User's Handbook. CRC press. If the Hansen Solubility Parameters are not found for a certain liquid vehicle in the aforementioned handbooks, other publications and / or data tables can be used. For example, the following can be mentioned: CRC Handbook of Solubility Parameters and Other Cohesion Parameters by Allan FM Barton. CRC Press (1983) or CRC Handbook of Solubility Parameters and Other Cohesion Parameters, par Allan FM Barton, 2nd edition (1991).
[0042] The remanent polarization was measured at 20° C. in an electric field of 100 MV / m using the Sawyer Tower method (LC2, manufactured by Radiant Tech. Co.).
[0043] <Fluorinated polymer> The fluorinated polymer comprises repeat units derived from vinylidene fluoride (abbreviated as VDF or VF2) and trifluoroethylene (abbreviated as TrFE or VF3).
[0044] The fluorinated polymer may in particular comprise a molar ratio of repeat units derived from vinylidene fluoride and trifluoroethylene of at least 50%, or at least 75%, or at least 80%, or at least 85%, relative to the total molar amount of all repeat units in the polymer.
[0045] The fluorinated polymer may contain repeat units other than those derived from vinylidene fluoride and trifluoroethylene. In particular, other repeat units may be derived from fluorinated monomers of formula (I). CX1X2=CX3Z-(I) [In the formula, each of X1, X2, and X3 is independently selected from H, F, and an alkyl group having 1 to 3 carbon atoms which may be partially or fully fluorinated, and Z is selected from Cl, Br, and I.]
[0046] The fluorinated polymer may in particular include one repeat unit derived from chlorotrifluoroethylene (CTFE), chlorofluoroethylene, in particular 1,1-chlorofluoroethylene (CFE), or a combination thereof.
[0047] In some embodiments, the fluorinated polymer may consist essentially of or consist of repeat units derived from vinylidene fluoride, trifluoroethylene, and optionally one or several units derived from a fluorinated monomer of formula (I).
[0048] The fluorinated polymer may be P(VDF-TrFE), P(VDF-TrFE-CTFE) or P(VDF-TrFE-CFE) in certain embodiments.
[0049] In a preferred embodiment, the molar ratio of trifluoroethylene repeat units is between 15% and 50%, preferentially between 16% and 35%, and most preferentially between 17% and 32%, relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units. Indeed, the fluorinated polymer has particularly advantageous ferroelectric properties over these ranges.
[0050] In a preferential embodiment, the fluorinated polymer may consist essentially of or may consist of repeat units derived from vinylidene fluoride, trifluoroethylene and optionally one or several repeat units derived from fluorinated monomers of formula (I), the molar ratio of trifluoroethylene repeat units being between 15% and 50%, preferentially between 16% and 35%, most preferentially between 17% and 32%, relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units, and the molar ratio of one or several fluorinated monomers of formula (I) being between 0 and 15%, in particular between 1 and 10%, relative to the total molar amount of all repeat units in the polymer.
[0051] In some particular embodiments, the fluorinated polymer can consist essentially of or consist of repeat units derived from vinylidene fluoride and trifluoroethylene, with the molar ratio of trifluoroethylene repeat units being 17% to 32% relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units. The molar ratio of trifluoroethylene repeat units can be in particular 17% to 23%, or 23% to 28%, or 28% to 32% relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units.
[0052] The melt flow index, measured according to ASTM D1238-20 at 230°C under a load of 10 kg, is 6 g / 10 min to 16 g / 10 min.
[0053] The melt flow index can be 6 g / 10 min or greater, 7 g / 10 min or greater, 8 g / 10 min or greater, 9 g / 10 min or greater, 10 g / 10 min or greater, or 11 g / 10 min or greater.
[0054] The melt flow index can be 16 g / 10 min or less, 15 g / 10 min or less, 14 g / 10 min or less, 13 g / 10 min or less, or 12 g / 10 min or less.
[0055] The melt flow index may in particular be between 8 g / 10 min and 15 g / 10 min, preferably between 10 g / 10 min and 14 g / 10 min.
[0056] In a particular embodiment, the melt flow index of the fluorinated polymer is from 11 g / 10 min to 13 g / 10 min.
[0057] The fluorinated polymers can be prepared by methods known per se, such as emulsion polymerization, suspension polymerization and solution polymerization. The fluorinated polymers can be prepared preferably by suspension polymerization, particularly preferably by suspension polymerization carried out in water.
[0058] In this embodiment, it is advantageous to add a suspending agent to the reaction medium. In particular, cellulose derivatives can be used, in particular cellulose ethers such as methylcellulose, ethylhydroxyethylcellulose or hydroxypropylmethylcellulose.
[0059] The reaction can be initiated by adding a radical polymerization initiator, which can in particular be an organic peroxide such as a peroxydicarbonate.
[0060] It may also be advantageous to add agents to the reaction medium that regulate the chain length: in particular, ethyl acetate or diethyl carbonate or alcohols such as, for example, isopropanol can be used.
[0061] <Liquid vehicle> The compatibility of the liquid vehicle with the fluorinated polymer can be characterized by the Hansen solubility parameters of the liquid vehicle and the fluorinated polymer.
[0062] For polymers containing repeat units derived from vinylidene fluoride and trifluoroethylene, such as those used in the present invention, it has been generally assumed in the art that the Hansen solubility parameter of a homopolymer of vinylidene fluoride can be used as a good approximation.
[0063] The inventors have particularly found that the evaluation carried out by MA, Jing and LARSEN, Raino Mikael. Comparative study on dispersion and interfacial properties of single walled carbon nanotube / polymer composites using Hansen solubility parameters. ACS applied materials & interfaces, 2013, Vol. 5, No. 4, p. 1287-1293, is particularly well suited for the selection of liquid vehicles to implement the present invention and to obtain improved electroactive properties for the polymer layers obtained from the compositions according to the invention.
[0064] MA calculated the Hansen solubility parameter for the homopolymer of vinylidene fluoride to be (17.1; 12.6; 10.6).
[0065] Liquid vehicle (δ d ;δ p ;δ h The distance (Ra) between the Hansen solubility parameters between the coordinate points (17.1;12.6;10.6) and (17.1;12.6;10.6) defines the following equation 1: (Ra) 2 =4·(δ d -17.1) 2 +(δ p -12.6) 2 +(δ h -10.6) 2 (Equation 1)
[0066] According to the present invention, the liquid vehicle is (Ra) 2 ≦22, preferentially (Ra) 2 ≦8, more preferentially (Ra) 2 ≦6, even more preferentially (Ra) 2 ≦4, most preferentially (Ra) 2 Hansen solubility parameter (δ) of ≦3 d ;δ p ;δ h ).
[0067] According to some embodiments, the liquid vehicle comprises, consists essentially of, or consists of dimethylsulfoxide, tetramethylurea, diethylene glycol monoethyl ether, N-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, trimethyl phosphate, triethyl phosphate, dimethylformamide, dimethylacetamide, and mixtures thereof.
[0068] Preferentially, the liquid vehicle comprises, consists essentially of, or consists of N-methyl-2-pyrrolidone, trimethyl phosphate, triethyl phosphate, dimethylformamide, dimethylacetamide, and mixtures thereof.
[0069] Even more preferentially, the liquid vehicle comprises, consists essentially of, or consists of triethyl phosphate, dimethylformamide, dimethylacetamide, and mixtures thereof.
[0070] Most preferentially, the liquid vehicle comprises, consists essentially of, or consists of dimethylformamide, dimethylacetamide, and mixtures thereof.
[0071] <Composition> The composition comprises, consists essentially of, or consists of one or several fluorinated polymers selected as above and one or more liquid vehicles selected as above.
[0072] The thickness of the polymer layer obtainable by coating the composition according to the invention and removing the liquid vehicle strongly depends on the mass concentration of the fluorinated polymer in the liquid vehicle: if the dry content of the formulation is too low, several printing steps must be carried out to achieve a sufficient layer thickness.
[0073] Thus, the mass concentration of the fluorinated polymer in the liquid vehicle may be 0.1% or more, preferably 1% or more, and most preferably 5% or more.
[0074] The mass concentration of the fluorinated polymer in the liquid vehicle can generally be 50% or less, preferably 30% or less, and most preferably 20% or less.
[0075] In some embodiments, the mass concentration of the fluorinated polymer in the liquid vehicle is 0.1% to 50%, preferably 1% to 30%, most preferably 5% to 20%. The mass concentration of the fluorinated polymer in the liquid vehicle may in particular be 5% to 9%, or 9% to 15%, or 15% to 20%.
[0076] The composition may optionally include one or more additives selected from, for example, surfactants, rheology modifiers, anti-aging agents, pigments or dyes, fillers (including nanofillers), or any residual additives used in the synthesis of the fluoropolymer.
[0077] In some embodiments, the composition may consist essentially of or consist of one or several fluorinated polymers selected as described above, one or more liquid vehicles selected as described above, and optionally one or more of such additives.
[0078] <Polymer layer made from the composition> As shown in the examples, the composition according to the invention makes it possible to produce polymer layers having improved electroactive properties, in particular a higher remanent polarization than previously known.
[0079] A polymer layer, in particular a film or coating, can be produced by deposition of a composition according to the invention on a substrate surface. Coating includes removal of the liquid vehicle of the composition, in particular by evaporation.
[0080] The substrate surface can be, for example, a glass surface or a silicon surface or a polymer surface or a metal surface.
[0081] Coating methods known in the art are, inter alia, spin coating, spray coating, bar coating, slot-die coating, dip coating, roll-to-roll printing, screen printing, flexographic printing, lithographic printing, and inkjet printing.
[0082] In some embodiments, as in the examples below, the coating method may be spin coating.
[0083] The polymer layer obtained by one of the aforementioned coating methods, for example spin-coating, may have an average thickness of 100 nm to 100 μm, preferably 500 nm to 50 μm, more preferably 750 nm to 20 μm, most preferably 1 μm to 10 μm. The average polymer layer may in particular be 1 μm to 3 μm, or 3 μm to 6 μm, or 6 μm to 10 μm.
[0084] To enhance the ferroelectric crystallinity, the resulting polymer layer may be subjected to an annealing step, which is usually carried out at a temperature above the Curie temperature and below the melting temperature of the fluorinated ferroelectric polymer according to the invention. Annealing can be carried out in particular by exposing the coating layer to a temperature of 50 to 200°C, preferably 80 to 180°C, more preferably 100 to 160°C, in particular 120 to 150°C.
[0085] The polymer layer may be poled as such or may already be integrated into an electronic device. It is well known that the higher the poling field, the higher the orientation of the dipoles perpendicular to the film direction and the higher the remanent polarization. However, the higher the poling field, the higher the risk of destruction during poling. Therefore, to guarantee the manufacturing yield, the electric field applied during poling must be limited. In general, a limited poling field is taken, in the range of 75-150 V / μm, preferably around 100 V / μm, which is above the coercive field of the ferroelectric copolymer (i.e. 50 V / μm).
[0086] <Electronic devices> The polymer layer according to the invention can be used as a layer in an electronic device, for example a sensor.
[0087] The sensitivity of a sensor comprising a polymer layer of a ferroelectric material is directly related to the remnant polarization of that material. Thus, the invention makes it possible to produce more sensitive sensors. More generally, the polymer layer according to the invention makes it possible to produce electronic devices with improved properties.
[0088] An electronic device means either a single electronic component or a set of electronic components that can perform one or more functions in an electronic circuit.
[0089] To build up an electronic component, the polymer layer of the invention can be coated with one or more additional layers, for example layers of polymers, semiconductor materials or metals, on a substrate in a manner known per se.
[0090] According to one particular variant, the electronic device is more particularly an optoelectronic device, that is to say capable of emitting, detecting or controlling electromagnetic radiation.
[0091] Examples of electronic devices or, where appropriate, optoelectronic devices relevant to the present invention are transistors (especially field effect), chips, batteries, solar cells, light emitting diodes (LEDs), organic light emitting diodes (OLEDs), sensors, actuators, transformers, tactile devices, microelectromechanical systems, electrocaloric devices and detectors.
[0092] According to a preferred variant, the polymer layer according to the invention can be used as an active layer between two metal or polymer electrodes in a sensor, in particular a piezoelectric sensor, which may in particular be a force, pressure, vibration or ultrasonic sensor.
[0093] Electronic and optoelectronic devices are used and integrated in many devices, appliances or electronic subassemblies, as well as in many objects and applications, such as televisions, mobile phones, rigid or flexible screens, thin film photovoltaic modules, lighting sources, energy sensors and transducers. EXAMPLES
[0094] <Production of P(VDF-TrFE) with different melt flow index> Four P(VDF-TrFE) (P1, P2, P3, P4) with a molar ratio of VDF:TrFE of 75:25 and different melt flow indexes were prepared by suspension polymerization by reacting trifluoroethylene (TrFE), vinylidene fluoride (VDF) in deionized water using methylhydroxypropylcellulose as dispersant, propyle peroxydicarbonate as initiator, and different weights of ethyl acetate, used as transfer agent, were added to adjust the melt flow index of the polymer.
[0095] The chemical composition of the polymer 1 Analyzed by 1 H NMR.
[0096] The peak melting temperature (Tm) was measured on the second heat using a temperature ramp of 10° C. / min.
[0097] The melt flow index (MFI) was measured at 230° C. under a load of 10 kg according to ASTM D1238-20 in a Flowmeter D4059 B marketed by Dynisco.
[0098] These properties of the four synthetic polymers are summarized in Table 1 below.
[0099] [Table 1]
[0100] <Manufacturing of films and sensors> To process by printing technique, the sensor based on P(VDf-TrFE) copolymer, 0.5 mL of polyvinylpyrrolidone (PVP)-melanin solution was spin-coated (2000 rpm, 1 min) on a polyethylene naphthalate (PEN) substrate (Panac Co., Ltd.) with a 1:1 PVP:melamine weight ratio (Sigma Aldrich Co., Ltd.) at 23 °C in ambient air to form a flat PVP layer, followed by annealing at 150 °C for 1 h. The thickness of the PVP layer was 800 nm.
[0101] This layer was then treated with an oxygen plasma cleaning apparatus (RIE-PC300, SAMCO Co., Ltd.) for 60 seconds to adjust the surface energy of the PVP layer. The radio frequency (RF) power of the plasma was set to 100 W, and the O2 flow rate was set to 30 sccm, respectively. Both the top and bottom Au electrodes were thermally coated to a thickness of 30 nm. Then, 0.5 mL of 12 wt% P(VDF-TrFE) solution and different solvents a) N,N-dimethylformamide (DMF, Sigma Aldrich Co., Ltd.), b) trimethyl phosphate (TMP, Kanto Chemical), c) isophorone (IPN, Sigma Aldrich Co., Ltd.), and d) cyclopentanone (CPN, Sigma Aldrich Co., Ltd.) were separately spin-coated (800–3000 rpm, 1 min) onto the surface at 23 °C in ambient air to construct a ferroelectric layer with a thickness of 1.5 μm. Next, annealing was carried out at 135° C. for 1 hour.
[0102] Finally, 0.5 mL of PVP solution was spin-coated (2000 rpm, 1 min) onto the assembly in ambient air to form a passivation layer with a thickness of 800 nm, followed by annealing at 135° C. for 1 h.
[0103] Table 2 below shows the Hansen solubility parameters of the four different solvents used and their calculated values according to Equation 1 (Ra) 2 Indicates the value of.
[0104] [Table 2]
[0105] The remanent polarization was measured at 20° C. and 100 V / μm using the Sawyer Tower method.
[0106] For each one of the examples, 15 devices were fabricated and characterized, and the remnant polarization shown in Table 3 below represents the average of the remnant polarization measured on the 15 devices.
[0107] [Table 3]
[0108] As shown in Table 3, the selection of the melt flow index and the Hansen solubility parameter, and therefore its calculated (Ra) 2 The solvent combination by value is 8.0 μC / cm measured in the laboratory at 20 °C and 100 V / μm using the Sawyer Tower method for a P(VDF-TrFE) copolymer with a VDF:TrFE molar ratio of 75:25. 2 This makes it possible to obtain an improved remanent polarization.
Claims
1. - a fluorinated polymer comprising repeat units derived from vinylidene fluoride and trifluoroethylene, the fluorinated polymer having a melt flow index, measured according to ASTM D1238-20 at 230°C under a load of 10 kg, of between 6 g / 10 min and 16 g / 10 min, preferably between 8 g / 10 min and 15 g / 10 min, more preferably between 10 g / 10 min and 14 g / 10 min; - (Ra) 2 Hansen solubility parameter (δ) of ≦22 d ; δ p ; δ h ) a liquid vehicle having a structure as defined by the formula: (Ra) 2 = 4 · (δ d - 17.1) 2 + (δ p - 12.6) 2 + (δ h - 10.6) 2 (Equation 1) A composition comprising:
2. 10. The composition of claim 1, wherein the fluorinated polymer also comprises one or more repeat units derived from a fluorinated monomer of formula (I). CX 1 X 2 =CX 3 Z-(I) [In the formula, X 1 , X 2 and X 3 are each independently selected from H, F and alkyl groups containing 1 to 3 carbon atoms which may be partially or fully fluorinated, and Z is selected from Cl, Br and I, preferably the fluorinated monomer of formula (I) is chlorotrifluoroethylene, chlorofluoroethylene, or a mixture thereof.
3. said fluorinated polymer essentially consists or consists of repeat units derived from vinylidene fluoride, trifluoroethylene and optionally one or several fluorinated monomers of formula (I), the molar ratio of trifluoroethylene repeat units being between 15% and 50%, preferentially between 16% and 35% and most preferentially between 17% and 32%, relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units in the polymer, 3. The composition according to claim 1 or 2, wherein the molar ratio of the one or several fluorinated monomers of formula (I) is between 0% and 15% relative to the total molar amount of all repeat units in the polymer.
4. 4. The composition according to claim 1, wherein the fluorinated polymer consists essentially of or consists of repeat units derived from vinylidene fluoride and trifluoroethylene, the molar ratio of trifluoroethylene repeat units being from 17% to 32% relative to the total molar amount of vinylidene fluoride repeat units and trifluoroethylene repeat units.
5. The liquid vehicle is (Ra) 2 ≦15, preferentially (Ra) 2 ≦8, preferentially (Ra) 2 ≦6, preferentially (Ra) 2 ≦4, most preferentially (Ra) 2 5. The composition according to claim 1, having a Hansen solubility parameter of ≦3.
6. the liquid vehicle is selected from the group consisting of dimethyl sulfoxide, tetramethyl urea, diethylene glycol monoethyl ether, N-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, trimethyl phosphate, triethyl phosphate, dimethylformamide, dimethylacetamide and mixtures thereof; Preferentially, N-methyl-2-pyrrolidone, trimethyl phosphate, triethyl phosphate, dimethylformamide, dimethylacetamide and mixtures thereof, More preferentially, triethyl phosphate, dimethylformamide, dimethylacetamide and mixtures thereof, Most preferentially, dimethylformamide, dimethylacetamide and mixtures thereof. The composition of any one of claims 1 to 5, consisting essentially of or consisting of:
7. The composition according to any one of claims 1 to 6, wherein the fluorinated polymer has a melt flow index, measured according to ASTM D1238-20 at 230°C under a load of 10 kg, of 11 g / 10 min to 13 g / 10 min.
8. The composition according to any one of claims 1 to 7, wherein the mass concentration of the fluorinated polymer in the liquid vehicle is from 0.1 to 50%, preferably from 1 to 30%, most preferably from 5 to 20%.
9. A polymeric layer obtained by a process comprising a coating step of a composition according to any one of claims 1 to 7, said coating step comprising removing said liquid vehicle from said composition.
10. 10. The polymer layer according to claim 9, wherein said coating step is carried out by one of the techniques selected from the group consisting of spin coating, spray coating, bar coating, slot-die coating, dip coating, roll-to-roll printing, screen printing, flexography, lithography, inkjet printing, preferably spin coating.
11. A polymer layer, in particular a film, according to claim 9 or 10 having an average thickness of from 100 nm to 100 μm, preferably from 500 nm to 50 μm, more preferably from 750 nm to 20 μm, most preferably from 1 μm to 10 μm.
12. The polymer layer according to any one of claims 9 to 11, wherein the process comprises annealing the fluorinated polymer below its melting temperature.
13. The polymer layer according to any one of claims 9 to 12, wherein the process comprises a poling step.
14. 14. An electronic device comprising a polymer layer according to any one of claims 9 to 13, preferably selected from a field effect transistor, a memory device, a capacitor, a sensor, an actuator, a microelectromechanical system, a wearable electrical device, a robotic sensor, and a tactile device.